Moral values in the wayang petruk dadi ratu - Ngatmin Abbas; Mukhlis Fathurrohman; Husna Nashihin; Muh. Hasbi Khilal Zuhri (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
This research aims to explore and analyze the moral values embedded in the play Petruk Dadi Ratu in Javanese wayang art. The research method applied is a literature review (library research), focusing on the analysis of wayang texts and the Javanese cultural context. The research findings indicate that the play encompasses moral values such as wisdom, honesty, and fair leadership. The study also reveals how the character Petruk, through his journey to become a queen, represents noble values within Javanese society. The implications of these findings provide profound insights into how wayang art serves as a medium for conveying moral values in Javanese culture.